2017
DOI: 10.5120/cae2017652575
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Two Level Unequal Error Protection Scheme for MP3 Transmission over LTE

Abstract: Long-Term Evolution (LTE) is a wireless broadband communication technology which is highly used for the transmission of data and voice over the internet. However, due to noise and other channel deteriorations, the transfer of data and voice over LTE is very challenging. With the phenomenal increase of data and voice traffic, the management of Quality of Service (QoS) is a challenging problem. This paper presents an enhanced audio transmission scheme with two levels of Unequal Error Protection (UEP) for audio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Bit positions 1 and 2 are favored for the systematic bits. The parity bits are placed on bit positions 3 to 6 as detailed in 17 . For 256-QAM, the first and second-bit positions are the most secured ones.…”
Section: Prioritized Qam Constellationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bit positions 1 and 2 are favored for the systematic bits. The parity bits are placed on bit positions 3 to 6 as detailed in 17 . For 256-QAM, the first and second-bit positions are the most secured ones.…”
Section: Prioritized Qam Constellationmentioning
confidence: 99%
“…Bits 5 and 6 are the least secure place. 17 For 256-QAM, each major quadrant can be partitioned into four minor quadrants. Each minor quadrant is like a 64-QAM constellation.…”
Section: Order Of Qam (M)mentioning
confidence: 99%
“…After that, numerous UEP schemes based on various forward error correction (FEC) codes [20–22] or modulations [23–25] are developed. UEP is most widely applied in the transmission of multimedia data like voices, images and videos [26–28], as they are usually progressive and easier to be prioritized. For example, for H.264 videos, the I‐frame data in a Group of Pictures (GOP) is more important than B/P‐frame data, hence it should be allocated more transmission power or stronger FEC codes to improve the overall quality of the videos at receivers.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced audio transmission scheme with two levels of UEP for MP3 over LTE was presented by Ragpot, Fowdur, and Soyjaudah (2017). For the first level of UEP, the unequal importance of the bits generated by an MP3 codec was exploited, that is they were divided into control information bits and scalefactor and subbands bits.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that with 16-quadrature amplitude modulation (QAM) at a turbo code rate of 1/2, the proposed two level UEP scheme provided a gain of 22.36 dB in average in SSNR over a conventional EEP one. This paper builds up on the work by Ragpot et al (2017) by investigating a new UEP scheme with prioritized QAM constellations mapping and two other UEP schemes exploiting the statistical distribution of the source symbols to map systematic bits onto QAM constellations. The MP3 compressed audio files are transmitted using both LTE and Wi-Fi systems.…”
Section: Introductionmentioning
confidence: 99%